Improvement of wood densification process via enhancing steam diffusion, distribution, and evaporation - Fang, Chang-Hua; Cloutier, Alain; Jiang, Z-Hui; He, Jia-Zhong; Fei, Ben-Hua (Bioresources, 2019)
Mechanical densification treatments make it possible to increase the density of low- or moderate-density woods, and thus a high mechanical strength of densified wood and high-value products can be obtained. The authors’ previous treatments showed that the diffusion and distribution of steam and the release of vapor inside densified wood were prevented to some extent during thermo-hydro-mechanical (THM) densification, causing the occurrence of protrusions, carbonization, blisters, and blows. This study aimed to overcome these problems. Based on the authors’ previous THM densification, different materials, such as fabric, metal mesh, metal foam, and sintered metal mesh laminate (SMML), were used to improve the process. Densification was tested on different wood species. The results showed that SMML was the preferable material for THM densification through enhancing diffusion and distribution of steam, and evaporation of moisture inside wood. No protrusion, carbonization, blisters, or blows were found after densification with SMMLs. The densified wood specimens showed uniform color and a neat surface.